Why Canadian unity matters and why Americans care : democratic pluralism at risk - Doran, Charles F. (University of Toronto Press, 2001)
Drawing on a variety of perspective, Charles Doran examines why Canadian unity is important not only to the United States but also to other liberal democracies around the world. In addition, he looks at the wider context of Quebec nationalism and the nature of the historical era that has shaped and conditioned the secessionist impulse.